PENGARUH BIAYA PRODUKSI TERHADAP PENDAPATAN PETANI DI KOPERASI UNIT DESA (KUD) PALAPA DESA MUARA BAHAN KECAMATAN SINGINGI HILIR KABUPATEN KUANTAN SINGINGI - Mela Rediana; Rina Selva Johan; Hendripides ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to determine the influence of production cost towards Farmers Income in the Village Unit Cooperatives (KUD) Palapa Village Muara Bahan District of Singingi Hilir Regency Kuantan Singingi. The research was conducted from April to june 2016. The method used is descriptive quantitative method. The population of this study was 397 smallholders, the sample in this study as many as 40 farmers sampling technique by using cluster sampling. The data collection technique using the method of documentation and interviews. Data analysis technique used is a simple linear regression. From hasl research obtained that simultaneous production costs affect the income of farmers in the village unit cooperatives Palapa. This is based on the results of analyzes, calculations show Fhitung> Ftabel (1034,471> 4,08). From coefficient determination calculating production costs affect the income of farmers amounted to 96.5% and the rest of its 3.5% influenced by other factors not examined.Keywords: Production Costs, Income Smallholders